2018
DOI: 10.1021/acsnano.7b06691
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chirality in Two-Dimensional Nanomaterials: Chiral 2D MoS2 Nanostructures

Abstract: Two-dimensional (2D) nanomaterials have been intensively investigated due to their interesting properties and range of potential applications. Although most research has focused on graphene, atomic layered transition metal dichalcogenides (TMDs) and particularly MoS2 have gathered much deserved attention recently. Here, we report the induction of chirality into 2D chiral nanomaterials by carrying out liquid exfoliation of MoS2 in the presence of chiral ligands (cysteine and penicillamine) in water. This proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 89 publications
0
96
0
Order By: Relevance
“…Different aspects of this phenomenon have been elucidated frequently in multiple excellent contributions for metallic [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and semiconducting nanoparticles. [99][100][101][102][103][104][105][106][107][108][109] Ma and coworkers summarized most of the works related to chirality transfer in 2017 where they considered four types of chirality in nanoparticles and gave examples of each. 110 The four types are the following: (1) geometrical chirality of the inorganic core, (2) geometrical chirality of the inorganic surface (also called chiral footprint), (3) geometrical chirality of the protecting shell, and (4) chiral field effect.…”
Section: Induced Chiralitymentioning
confidence: 99%
“…Different aspects of this phenomenon have been elucidated frequently in multiple excellent contributions for metallic [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and semiconducting nanoparticles. [99][100][101][102][103][104][105][106][107][108][109] Ma and coworkers summarized most of the works related to chirality transfer in 2017 where they considered four types of chirality in nanoparticles and gave examples of each. 110 The four types are the following: (1) geometrical chirality of the inorganic core, (2) geometrical chirality of the inorganic surface (also called chiral footprint), (3) geometrical chirality of the protecting shell, and (4) chiral field effect.…”
Section: Induced Chiralitymentioning
confidence: 99%
“…For instance, chiral 2D MoS 2 was fabricated by introducing the chiral ligands cysteine and penicillamine during the liquid exfoliation of MoS 2. Further, surface‐anchored chiral molecules on nanoparticles exert different chiral preferences to modulate cellular uptake and cell adhesion in bacterial and mammalian cells, which influence the biological effects of the nanoparticles on cytotoxicity, autophagy, gene editing, and metabolism . Gong et al., demonstrated that the d ‐glutamic acid modified graphene quantum dots showed highly selective penetration into the bacterial cell membrane over mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…These chiral molecules and their mirror images (enantiomers) exhibit opposite handedness when interacting with circularly polarized light, as well as different chemical and biological performance. Inspired by chiral molecular structures, researchers are developing strategies to build artificial chiral materials by mimicking molecular structures using functional materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Specifically, metal nanomaterials exhibit tailorable optical properties upon excitation of surface plasmons and become one of the most promising components to realize of chiral optical metamaterials [15,16].…”
Section: Introductionmentioning
confidence: 99%